The dynamics of poor urban areas - analyzing morphologic transformations across the globe using Earth observation data. (December 2020) - Kraff, Nicolas J.; Wurm, Michael; Taubenböck, Hannes
Abstract: The urban environment is in constant motion, mostly through construction but also through destruction of urban elements. While formal development is a process with long planning periods and thus the built landscape appears static, informal or spontaneous settlements seem to be subject to high dynamics in their ever unfinished urban form. However, the dynamics and morphological characteristics of physical transformation in such settlements of urban poverty have been hardly empirically studied on a global scale or temporal consistent foundation. This paper aims at filling this gap by using Earth observation data to provide a temporal analysis of built-up transformation over a period of ~7 years in 16 documented manifestations of urban poverty. This work applies visual image interpretation using very high resolution optical satellite data in combination with in-situ- and Google Street View images to derive 3D city models. We measure physical spatial structures through six spatial morphologic variables - number of buildings, size, height, orientation, heterogeneity and density . Our temporal assessment reveals inter- as well intra-urban differences and we find different, yet generally high morphologic dynamic across study sites. This is expressed in manifold ways: from demolished and reconstructed areas to such where changes appeared within the given structures. Geographically, we find advanced dynamics among our sample specifically in areas of the global south. At the same time, we observe a high spatial variability of morphological transformations within the studied areas. Despite partly high morphologic dynamics, spatial patterns of building alignments, streets and open spaces remain predominantly constant. Highlights: An empirical panel study that reveals morphologic dynamics over a 7-year time period of urban poverty areas across the globe. Generating 3-D models, based on Level-of-Detail-1 visual image interpretation of urban poverty areas (slums, ghettos, etc.). Development of spatial variables and indicators that allow for a spatiotemporal characterization. Inter- and intra-urban assessment of temporal transitions of single building morphologies and the pattern of the settlement.